Just Doing Business or Doing Just Business: Google, Microsoft, Yahoo! and the Business of Censoring China’s Internet - Dann, Gary Elijah (Journal of business ethics, 2008)
This paper addresses the criticism recently directed at Internet companies who have chosen to do business in China. Currently, in order to conduct business in China, companies must agree to the Chinese government’s rule of self-censoring any information the government deems inappropriate. We start by explaining how some of these companies have violated the human rights of Chinese citizens to freely trade information. We then analyze whether the justifications and excuses offered by these companies are sufficient to absolve them of moral responsibility. We argue that both justifications and excuses offered are insufficient. Wilfully abiding by unjust laws, albeit necessary to do business in China, should not trump moral actions that protect rights.